2012
DOI: 10.1186/1745-6215-13-182
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea and dengue control in rural primary schools in Colombia: study protocol for a randomized controlled trial

Abstract: BackgroundDiarrheal diseases and dengue fever are major global health problems. Where provision of clean water is inadequate, water storage is crucial. Fecal contamination of stored water is a common source of diarrheal illness, but stored water also provides breeding sites for dengue vector mosquitoes. Poor household water management and sanitation are therefore potential determinants of both diseases. Little is known of the role of stored water for the combined risk of diarrhea and dengue, yet a joint role w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
2
12
0
3
Order By: Relevance
“…However, recogition of the importance of dengue in semi-urban and rural areas is increasing [15,20]. Some studies have suggested that transmission at rural schools may play a role [21,22]. Additionally, lack of access to tap water and use instead of discarded water storage jars and concrete tanks have been implicated as important breeding sites for the vector [23], and mosquito populations may, therefore, be higher in some rural than urban areas [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, recogition of the importance of dengue in semi-urban and rural areas is increasing [15,20]. Some studies have suggested that transmission at rural schools may play a role [21,22]. Additionally, lack of access to tap water and use instead of discarded water storage jars and concrete tanks have been implicated as important breeding sites for the vector [23], and mosquito populations may, therefore, be higher in some rural than urban areas [24].…”
Section: Discussionmentioning
confidence: 99%
“…Barrera, et al, found that the most important factor determining DENV endemicity was the practice of water storage, which provided a source of mosquito breeding sites (19), especially when the water was not frequently replaced (20). In addition, improvements to water distribution infrastructure have been shown to decrease the incidence of vector-transmitted diseases by decreasing the amount of exposure to infected bites (21). Production of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria for schools and pupils are described in detail in Overgaard et al . [54]. In brief, large schools (>100 pupils and >five grades) were excluded due to different teaching strategies, teacher-student dynamics, and number of pupils compared to primary schools.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the interventions are provided in Overgaard et al . [54]. No dengue or diarrhea interventions by governmental or other actors were carried out in the rural schools during the study period.…”
Section: Methodsmentioning
confidence: 99%